Study on the performance of drip emtters - JOSNI P ROSHNI P. SEBASTIAN SUSMITHA R. NAIR; Er. E. K Kurien (Guide) (Tavanur 1994 Department of Irrigation and Drainage Engineering)
Study on the performance of drip emtters
Study on the performance of drip emtters